Activity of Sodium Trimetaphosphate Nanoparticles on Cariogenic-Related Biofilms In Vitro - Amarante, Viviane de Oliveira Zequini [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Sampaio, Caio [UNESP]; de Morais, Leonardo Antônio [UNESP]; de Camargo, Emerson Rodrigues; Monteiro, Douglas Roberto [UNESP]; Pessan, Juliano Pelim [UNESP]; Hosida, Thayse Yumi [UNESP] (MDPI, 2023)
In light of the promising effect of sodium trimetaphosphate nanoparticles (TMPn) on dental enamel, in addition to the scarce evidence of the effects of these nanoparticles on biofilms, this study evaluated the activity of TMPn with/without fluoride (F) on the pH, inorganic composition and extracellular matrix (ECM) components of dual-species biofilms of Streptococcus mutans and Candida albicans. The biofilms were cultivated in artificial saliva in microtiter plates and treated with solutions containing 1% or 3% conventional/microparticulate TMP (TMPm) or TMPn, with or without F. After the last treatment, the protein and carbohydrate content of the ECM was analyzed, and the pH and F, calcium (Ca), phosphorus (P), and TMP concentrations of the biofilms were determined. In another set of experiments, after the last treatment, the biofilms were exposed to a 20% sucrose solution, and their matrix composition, pH, and inorganic component contents were evaluated. 3% TMPn/F significantly reduced ECM carbohydrate and increased biofilm pH (after sucrose exposure) than other treatments. Also, it significantly increased P and F levels before sucrose exposure in comparison to 3% TMPm/F. In conclusion, 3% TMPn/F affected the biofilm ECM and pH, besides influencing inorganic biofilm composition by increasing P and F levels in the biofilm fluid.
Keywords: biofilms; Candida albicans; dental caries; extracellular matrix; fluorides; nanotechnology; phosphates; Streptococcus mutans